ANALISIS PENGARUH PROFITABILITAS (ROE) DAN LIKUIDITAS (FDR) TEHADAP KINERJA KEUANGAN (ROA) PERBANKAN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN (2018-2022) - Herlina, Tati; Arjo, Eka Pratiwi; Wiranawata, Hilmi (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
The aim of this research was to determine the influence of Profitability (ROE) and Liquidity (FDR) on the Financial Performance (ROA) of Sharia Banks listed on the Indonesia Stock Exchange for the 2018-2022 period. The panel data regression analysis method used was a quantitative method. The results of this research showed that the variables profitability (ROE) and liquidity (FDR) simultaneously influence the financial performance (ROA) of sharia banking listed on the BEI for the 2018-2022 period. Partially, Profitability (ROE) influenced Financial Performance (ROA) in sharia banking listed on the IDX for the 2018-2022 period. Partially, the influence of liquidity (FDR) on financial performance (ROA) in sharia banking listed on the IDX for the 2018-2022 period. The R-squared (R2) value obtained was 0.826759 or 82.68%, this showed that the percentage influence of the Profitability (X1) and Liquidity (X2) variables on Financial Performance (Y) was 83.68% while the remaining 17.32% in influence other factors not studied.